Stochastic geometry-based modeling of electromagnetic field with imperfect beam alignment - Muhammad, Nor Aishah; Radzwan, Nur Aiyani; Seman, Norhudah; Saris, Nur Najahatul Huda; Anwar Apandi, Nur Ilyana; Daud, Nurul Ashikin (2024)
Installing more base stations can enhance the cov- erage and throughput of the cellular networks, but increasing